Optimizing Broiler Production: A Narrative Review of The Role of Flock Age and Maternal Nutrition in Hatchability, Embryo Development, and Chick Quality - Mabotha, Temosho R.; Nephawe , Khathutshelo A.; Idowu, Peter A.; Mpofu, Takalani J. (Jurnal Sain Peternakan Indonesia, 2026)
Globally, chicken production continues to grow, and the consumption of chicken products is surpassing that of other animal products. Embryo mortality, poor hatchability, and chick quality remain the biggest challenges in both natural and artificial incubation. This review investigates the multifaceted effects of flock age and maternal nutrition on key reproductive parameters in broiler chickens, including hatchability, embryonic development, and chick quality. Aging flocks negatively impact reproductive performance and subsequent chick quality; proper management and optimizing storage parameters can mitigate these effects. The age of the flock and maternal nutrition collectively influence hatchability, which in turn determines the potential for successful embryo development and ultimately, the quality of the day-old chick, highlighting the interconnectedness of breeder management and progeny performance. Synthesizing complex biological and nutritional interactions is crucial for understanding the key elements that contribute to optimal poultry production outcomes. By optimizing maternal nutrition, the industry can expect improvements in hatchability, reduced early chick mortality, and enhanced overall chick quality, resulting in significant economic benefits. Furthermore, this review would inform and refine industry practices in broiler breeder management. Poultry researchers and producers can synthesize this information to formulate more effective and economically viable feeding programs for breeder flocks.